Game-Based and Teaching Games for Understanding Approaches in Badminton Learning at School: A Systematic Review - Hendya Alif Junanda; Dedi Supriadi; Vicki Ahmad Karisman (Universitas Majalengka, 2025)
Badminton is a net/wall game commonly taught in school physical education. It requires not only technical proficiency but also tactical awareness, decision-making, spatial understanding, and meaningful game performance. However, badminton instruction in schools is still often dominated by isolated technical drills, which may limit students' ability to transfer skills into authentic game situations. Game-Based Approaches and Teaching Games for Understanding (TGfU) offer a pedagogical alternative by placing modified games, tactical problems, questioning, and contextualized skill execution at the center of learning. This systematic review aims to synthesize recent evidence on the implementation and learning outcomes of game-based and TGfU approaches in school badminton learning. The review was guided by PRISMA 2020. An exploratory search was conducted for articles published between January 2021 and April 2026 using combinations of keywords related to badminton, TGfU, game-based learning, modified games, school students, and physical education. After duplicate removal and title-abstract screening, four potentially relevant studies were examined in full text for preliminary synthesis. The available evidence suggests that game-based and TGfU-related approaches are promising for integrating technical skill development, tactical understanding, decision-making, game performance, and student engagement. The most directly relevant study showed that situated game teaching through set plays produced greater improvement in tactical knowledge, technical ability, and badminton game performance than a technique-focused approach. Game-based and TGfU approaches are pedagogically relevant for badminton learning in schools because they connect skill learning with tactical meaning and active student participation. Nevertheless, the number of recent badminton-specific studies remains limited, indicating the need for more rigorous, transparent, and sport-specific intervention research.